Експресія гена RET в післячорнобильських пухлинах щитовидної залози - Воскобойник, Л.Г.; Богданова, Т.І.; Тронько, М.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
The expression of RET gene that encodes a transmembrane receptor with tyrosine kinase activi- ty, was studied on 59 post-Chernobyl thyroid tumors (35 papillary carcinomas and 24 follicular adenomas). It is shown that the majority of tumors, both benign and malignant, exhibits RET expression. The presence of gene RET in thyroid tumors was not associated with their hi- stological structure, invasiveness, tumor’s sizes, and the age and sex of patients. Nevertheless, the occurrence of RET expression (which is not expressed in normal thyroid cells) in the great part of post-Chernobyl thyroid tumors suggests a potential role of RET in the development of thyroid neoplasms, both benign and malignant.